Protective Impacts of Chlorella vulgaris on Cisplatin-Induced Toxicity in Liver, Kidney, and Spleen of Rats: Role of Oxidative Stress, Inflammation, and Nrf2 Modulation - Layla A. Almutairi; Ebtehal G. Abdelghaffar; Hany A. Hafney; Hala M. Ebaid; Sahar A. Alkhodair; Aly A. M. Shaalan; Heba N. Gad EL-Hak (Life, 2025)
Cisplatin is a widely utilized chemotherapy drug effective against various cancers, yet its use is often constrained by severe toxicity to healthy organs, including the liver, kidneys, and spleen. This study explored the protective role of Chlorella vulgaris, a microalga known for its antioxidant and anti-inflammatory properties, against cisplatin-induced organ damage. The research focused on modulating oxidative stress, inflammation, and the Nrf2 signaling pathway. The experimental design included four groups: a control group receiving saline, a cisplatin group administered 1.34 mg/kg weekly for three months, a C. vulgaris group receiving 150 mg/kg daily, and a combined cisplatin/Chlorella vulgaris group. Cisplatin treatment significantly elevated oxidative stress markers, such as lipid peroxidation and nitric oxide, while increasing pro-inflammatory cytokines (TNF-α, IL-12, IL-6) and reducing antioxidant capacity. Additionally, liver and kidney function markers were markedly impaired, and histopathological analysis revealed structural damage in the liver, kidneys, and spleen. Conversely, C. vulgaris supplementation mitigated these effects, restoring oxidative stress markers, cytokine levels, and organ function to near-normal values. Microscopic examination confirmed that Chlorella vulgaris effectively prevented cisplatin-induced structural damage. Notably, while cisplatin increased Nrf2 expression as an adaptive response to oxidative stress, C. vulgaris attenuated this effect, reflecting its potent antioxidant capabilities.